Implementation of OJS Based iJC Media E-Journal System at University of Pramita Indonesia - Mumen, Md. Abdul; Oganda, Fitra Putri; Lutfiani, Ninda; Handayani, Indri (APTISI Transactions on Management (ATM), 2020)
The increasing development of information technology in the era of 5.0 can provide information that is informative and very easy to obtain in the form of electronics. But not at Pramita University of Indonesia in managing journals or other scientific works still using conventional or manual methods that cause the main problem that is causing increased costs and time, the data can be separated because the old data is not archived properly and the management of scientific works also does not meet the specified requirements by Ristekdikti with regard to Journal Accreditation which requires that journals be managed online because that will be easier and faster. With the iJC (iLearning Journal Center) can publish journals online, make it easier for users to submit journals, change the management of ejournal to be more distributed and can simplify the process of submitting manuscripts, reviewing, editing, until the publication stage and by using iLearning Journal Center will produce e quality journal. In this study, researchers used several methods, namely the method of observation and study of literature and using Flowcharts.